Pengaruh Biaya Produksi dan Current Ratio Terhadap Pertumbuhan Laba Perusahaan Subsektor Food and Beverage - Devita Sari; Sri Wahyuni Jamal; Fenty Fauziah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The availability of raw materials for the Food and Beverage industry is a sector that continues to grow and contributes greatly to supporting national economic growth. This opens up opportunities for Food and Beverage Subsector companies to increase their profit growth. Therefore, in increasing profit growth, it can be seen from two factors, namely production costs and current ratio. This study aims to analyze the effect of production costs and current ratio on profit growth in Food and Beverage Subsector companies. Data were collected through documentation techniques, which had a sample of 7 companies for 9 years (2015 - 2023) and a total of 63 data using purposive sampling techniques. This study uses a quantitative approach with multiple linear regression analysis techniques. The results of the study show that production costs have a smaller t-count value than the t table, which is -2,400> 2,000 and a sig. value. 0.019 < 0.05 or significance value is smaller than 0.05, then the production cost variable (X1) is stated to have a significant effect on profit growth (Y). While the current ratio has a calculated t value that is smaller than the t table value, which is 0.143 < 2,000 and a sig. value of 0.887 > 0.05 or significance value is greater than 0.05, then the current ratio variable (X2) is stated to have no significant effect on profit growth (Y). The implication of this study is the importance of managing operational costs efficiently. Companies should be careful in making financing decisions, because production costs that are too high can hinder profit growth. And efficient management of current assets remains important to maintain financial stability.